Method for preparing membrane electrode through one-step two-section hot-pressing transfer printing and membrane electrode

Through the one-step two-stage hot press transfer method, the problem of difficult to control the catalyst adhesion strength and deformation of the transfer substrate is solved, and the high transfer rate and yield of the film electrode are achieved, and the performance and life of the film electrode are improved.

CN119812412AActive Publication Date: 2025-04-11SHANGHAI INST OF SPACE POWER SOURCES

Patent Information

Application Number
CN202411818990.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-11
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

When preparing film electrodes with existing thermal transfer methods, the catalyst adhesion strength is difficult to control, and the deformation of the transfer substrate after hot pressing cannot be reused, resulting in low yield and high cost of film electrodes, and poor uniformity in platinum load distribution affects performance and life.

Method used

The first step and two-stage hot press transfer method is adopted. The first hot pressing treatment stage is a long time low-pressure heat treatment, and the second hot pressing treatment stage is a shorter time high-pressure heat treatment. Through this process, the cathode catalytic layer and the anode catalytic layer form close contact with the proton exchange film, which improves the transfer rate and retains the pore structure of the catalytic layer to the greatest extent and reduces the mass transfer impedance.

Benefits of technology

The 100% transfer rate of the catalytic layer is achieved, the yield and service life of the film electrode are improved, and the peak power density of the film electrode is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812412A_ABST
    Figure CN119812412A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a membrane electrode through one-step two-section hot-pressing transfer printing. Comprising the following steps: S1, coating a first transfer printing substrate with cathode catalyst slurry to form a cathode catalyst layer, and coating a second transfer printing substrate with anode catalyst slurry to form an anode catalyst layer; s2, the first tiled layer, the second transfer printing base material with the anode catalyst layer, the proton exchange membrane, the first transfer printing base material with the cathode catalyst layer and the second tiled layer are sequentially stacked and tiled on a hot press, first hot pressing treatment and second hot pressing treatment are sequentially executed, and the cathode catalyst layer and the anode catalyst layer are arranged close to the proton exchange membrane; wherein the treatment pressure of the first hot-pressing treatment is smaller than that of the second hot-pressing treatment, and the treatment time of the first hot-pressing treatment is larger than or equal to that of the second hot-pressing treatment. According to the method, the initial pore structure of the catalyst layer can be reserved to the greatest extent while the transfer printing rate of the catalyst layer is improved, and the peak power density of the membrane electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a method for preparing a membrane electrode by utilizing a one-step two-stage hot pressing transfer and a membrane electrode. Background Art

[0002] When using the thermal transfer method to prepare the membrane electrode assembly of a proton exchange membrane fuel cell, it is necessary to transfer the catalyst layer to the proton exchange membrane through a transfer substrate, and then remove the transfer substrate to obtain a catalyst-coated membrane. However, after actual application, it was found that this method has the following shortcomings: the catalyst is affected by temperature and pressure, so its adhesion strength on the proton exchange membrane cannot be controlled, and during hot pressing, the catalyst on the edge of the membrane and the transfer substrate cannot be completely transferred to the proton exchange membrane due to uneven force, thereby reducing the yield rate of the membrane electrode; at the same time, the transfer substrate is often deformed due to hot pressing and cannot be reused, which increases the cost of membrane electrode production.

[0003] In recent years, with the continuous research and development of researchers, a method for preparing membrane electrodes by thermal transfer has been disclosed, which combines the ultrasonic spraying process and the thermal transfer process. However, the following problems still exist: this method includes the ultrasonic spraying process, which is relatively time-consuming, and the platinum loading distribution uniformity of the membrane electrode prepared by this method is poor, which seriously affects the performance and life of the membrane electrode.

[0004] Therefore, developing a new method for preparing membrane electrodes by thermal transfer to improve the transfer rate of the catalytic layer and increase the yield and service life of the membrane electrode is an urgent problem to be solved in this field. Summary of the invention

[0005] The purpose of the present invention is to provide a novel method for preparing a membrane electrode by hot pressing transfer, so as to improve the transfer rate of the catalytic layer, thereby improving the yield rate and service life of the membrane electrode.

[0006] To achieve the above object, the present invention first provides a method for preparing a membrane electrode by one-step two-stage hot pressing transfer, comprising the following steps:

[0007] S1, coating a cathode catalyst slurry onto a first transfer substrate to form a cathode catalyst layer, and coating an anode catalyst slurry onto a second transfer substrate to form an anode catalyst layer;

[0008] S2, stacking and laying the first tiling layer, the second transfer substrate with the anode catalyst layer formed thereon, the proton exchange membrane, the first transfer substrate with the cathode catalyst layer formed thereon, and the second tiling layer on a hot press in sequence, and performing a first hot pressing treatment and a second hot pressing treatment in sequence, wherein the cathode catalyst layer and the anode catalyst layer are arranged close to the proton exchange membrane;

[0009] The processing pressure of the first hot pressing treatment is less than the processing pressure of the second hot pressing treatment, and the processing time of the first hot pressing treatment is greater than or equal to the processing time of the second hot pressing treatment.

[0010] Preferably, the treatment pressure of the first hot pressing treatment is 1 kg / cm 2 -10kg / cm 2 The processing temperature is 120℃-170℃; the processing time is 60 seconds-300 seconds.

[0011] Preferably, the treatment pressure of the second hot pressing treatment is 10 kg / cm 2 -80kg / cm 2 The processing temperature is 120℃-170℃; the processing time is 10 seconds-60 seconds.

[0012] Preferably, the first laying layer and the second laying layer are made of a porous material, and the porous material includes: any one of carbon paper, carbon cloth, high temperature paper or thin steel plate.

[0013] Preferably, the areas of the first tiling layer and the second tiling layer are greater than or equal to the area of ​​the proton exchange membrane.

[0014] Preferably, the thickness of the first tiling layer and the second tiling layer is 10 μm to 300 μm.

[0015] Preferably, the proton exchange membrane has a thickness of 40 μm to 160 μm.

[0016] Preferably, in step S1, the cathode catalyst slurry and the anode catalyst slurry are coated on the first transfer substrate and the second transfer substrate respectively by slit coating.

[0017] Preferably, the method further comprises: S3, removing the first transfer substrate and the second transfer substrate in the product of step S2, pasting carbon paper on both sides, sealing the frame, and obtaining a membrane electrode by stamping.

[0018] Another aspect of the present invention provides a membrane electrode assembly, wherein the membrane electrode is manufactured by the above method.

[0019] Compared with the prior art, the beneficial effects of the present invention include at least:

[0020] The invention provides a method for preparing a membrane electrode by one-step two-stage hot pressing transfer, comprising: a first hot pressing treatment stage and a second hot pressing treatment stage.

[0021] Among them, the first hot pressing treatment stage is a long-term low-pressure heat treatment process. In this stage, the long-term heat and low pressure make the proton exchange membrane flat; at the same time, the long-term heat makes the cathode catalyst layer and the anode catalyst layer soft and melted, increasing their fluidity. On this basis, combined with the low pressure effect, the cathode catalyst layer and the anode catalyst layer can form an initial close contact with the proton exchange membrane, which not only makes up for the problem of insufficient material contact tightness due to the shortening of the subsequent high-pressure heat treatment time, but more importantly, the close contact between the cathode catalyst layer, the anode catalyst layer and the proton exchange membrane is a close-fitting contact with the shape, and there is no gap between the interfaces, thereby improving the transfer rate of the cathode catalyst layer and the anode catalyst layer to the proton exchange membrane, and the transfer rate can reach 100%.

[0022] The second hot pressing treatment stage is a relatively short high-pressure heat treatment process. This stage reduces the high-pressure action time on the cathode catalyst layer and the anode catalyst layer, retains the initial pore structure of the cathode catalyst layer and the anode catalyst layer to the greatest extent, reduces the mass transfer impedance of the membrane electrode, and enables the membrane electrode prepared by the method of the present invention to have a higher peak power density. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flow chart of the method for preparing membrane electrode by one-step two-stage hot pressing transfer.

[0024] Figure 2 This is a physical picture of the membrane electrode prepared in Example 1.

[0025] Figure 3 This is a physical picture of the membrane electrode prepared in Example 2.

[0026] Figure 4 This is a physical picture of the membrane electrode prepared in Example 3.

[0027] Figure 5 This is a physical picture of the membrane electrode prepared in Comparative Example 1.

[0028] Figure 6 The thickness comparison of the membrane electrodes prepared in Examples 1-3 and the comparative example.

[0029] Figure 7 The performance test comparison of the membrane electrode of Example 1 and Comparative Examples 1-2 applied to a low-temperature hydrogen-oxygen proton exchange membrane fuel cell is shown. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0031] As mentioned above, the existing thermal transfer process for preparing proton exchange membrane fuel cell membrane electrode assemblies has problems such as the catalyst cannot be completely transferred to the proton exchange membrane, thereby affecting the membrane electrode yield, and the transfer substrate undergoes thermal compression deformation and cannot be reused. It is urgent to develop a new thermal transfer method for preparing membrane electrodes to improve the transfer rate of the catalyst layer and improve the membrane electrode yield.

[0032] To achieve the above-mentioned purpose, the applicant of the present invention has provided a method for preparing membrane electrode by hot pressing transfer in one step and two stages after extensive research. Figure 1 As shown, the following steps are included:

[0033] S1, coating a cathode catalyst slurry onto a first transfer substrate to form a cathode catalyst layer, and coating an anode catalyst slurry onto a second transfer substrate to form an anode catalyst layer.

[0034] The first transfer substrate and the second transfer substrate are selected from one or both of PTFE film (polytetrafluoroethylene film) and glass fiber paper, and have a thickness of 80 μm-150 μm.

[0035] The cathode catalyst slurry and the anode catalyst slurry are conventional compositions in the art and may include a cathode catalyst (or anode catalyst), a binder and a solvent. Among them, the cathode catalyst may be one or two of platinum black, carbon-supported platinum carbon, and carbon-supported platinum cobalt catalysts. In the cathode catalyst, the content of platinum may range from 20wt% to 100wt%, and the content of carbon may range from 0wt% to 80wt%; the anode catalyst may be a carbon-supported platinum carbon catalyst, and in the anode catalyst, the content of platinum may range from 10wt% to 40wt%, and the content of carbon may range from 60wt% to 90wt%; the binder may be an ionic polymer, such as Nafion D2020, Nafion D520, Nafion D521, etc.; the solvent may be one or more of isopropanol, ethanol, n-propanol and water. It should be noted that the preparation method of the cathode catalyst slurry or the anode catalyst slurry can be prepared by referring to the conventional preparation method in the art, and will not be repeated here.

[0036] In some embodiments, after the cathode catalyst slurry and the anode catalyst slurry are prepared, the cathode catalyst slurry and the anode catalyst slurry are respectively coated onto the first transfer substrate and the second transfer substrate by a slit coating method, and then dried to form a cathode catalyst layer and an anode catalyst layer. The slit coating method is beneficial to ensure uniform coating of the catalyst slurry, and the catalyst utilization rate can be as high as 90% or more; in other embodiments, other coating processes in the field can also be used, which will not be elaborated here.

[0037] In some embodiments, the platinum loading in the cathode catalyst layer is set to 0.3 mg / cm 2 -1.0mg / cm2 The platinum loading in the anode catalyst layer was set to 0.1 mg / cm 2 -0.3mg / cm 2 The specific load setting depends on the actual application requirements.

[0038] S2, stacking and laying the first flat layer, the second transfer substrate formed with an anode catalyst layer, the proton exchange membrane, the first transfer substrate formed with a cathode catalyst layer, and the second flat layer in sequence on a hot press, and performing a first hot pressing treatment and a second hot pressing treatment in sequence, wherein the cathode catalyst layer and the anode catalyst layer are arranged close to the proton exchange membrane, wherein the processing pressure of the first heat treatment process is less than the processing pressure of the second hot pressing process, and the processing time of the first heat treatment process is greater than or equal to the processing time of the second hot pressing process.

[0039] As an example, the treatment pressure of the first hot pressing treatment is 1 kg / cm 2 -10kg / cm 2 The treatment temperature is 120°C-170°C, the treatment time is 60 seconds-300 seconds; the treatment pressure of the second hot pressing treatment is 10kg / cm 2 -80kg / cm 2 The processing temperature is 120℃-170℃; the processing time is 10 seconds-60 seconds.

[0040] In some embodiments, the proton exchange membrane comprises a perfluorosulfonic acid type proton exchange membrane, and the thickness of the proton exchange membrane is 40 μm to 160 μm.

[0041] It should be pointed out that the proton exchange membrane that has been activated in advance (for example, the perfluorosulfonic acid type proton exchange membrane, which needs to be activated before the catalyst layer hot pressing transfer process) is usually uneven and has wrinkles, especially when the proton exchange membrane is thicker, the unevenness is higher. Therefore, the prior art usually adopts a high-pressure and long-term heat treatment method to pre-flatten the activated proton exchange membrane, and then transfers the catalyst layer with the cathode catalyst layer and the anode catalyst layer through high-pressure and long-term heat treatment, but two long-term high-pressure heat treatments will seriously affect the quality and performance of the proton exchange membrane; More importantly, even if the proton exchange membrane is pre-flattened by high-pressure and long-term treatment, the membrane cannot be 100% flat, and there are still some wrinkles. During the subsequent high-pressure heat treatment transfer, because the proton exchange membrane and the catalyst on the transfer substrate are subjected to uneven force, further wrinkles and bubbles are generated, and ultimately the catalyst layer cannot be completely transferred to the proton exchange membrane.

[0042] Different from the prior art, the present invention divides the heat treatment transfer process of the catalyst layer into two stages:

[0043] (1) First is the first hot pressing treatment stage: This stage is a long-term low-pressure heat treatment process. In this stage, the long-term heat and low pressure make the proton exchange membrane flat; at the same time, the long-term heat makes the cathode catalyst layer and the anode catalyst layer soft and melted, and retains a certain fluidity under low pressure (it can be understood that under high-pressure heat treatment, even if the catalyst layer becomes soft due to heat, the high pressure limits its fluidity and cannot achieve the conformal close fit between the catalyst layer and the proton exchange membrane). The cathode catalyst layer and the anode catalyst layer can form an initial conformal close contact with the proton exchange membrane, which not only makes up for the problem of insufficient material contact tightness due to the shortening of the subsequent high-pressure heat treatment time, but more importantly, the close contact between the cathode catalyst layer, the anode catalyst layer and the proton exchange membrane is a conformal close fit contact, and there is no gap between the interfaces, thereby improving the transfer rate of the cathode catalyst layer and the anode catalyst layer to the proton exchange membrane, and the transfer rate can reach 100%.

[0044] (2) The second hot pressing treatment stage is followed: This stage is a short-term high-pressure heat treatment process. This stage reduces the high-pressure action time on the cathode catalyst layer and the anode catalyst layer, retains the initial pore structure of the cathode catalyst layer and the anode catalyst layer to the greatest extent, reduces the mass transfer impedance of the membrane electrode, and enables the membrane electrode prepared by the method of the present invention to have a higher peak power density.

[0045] Among them, the first flat layer and the second flat layer help to flatten the proton exchange membrane and the cathode catalyst layer and the anode catalyst layer bonded to the proton exchange membrane during the first hot pressing process and the second hot pressing process, reduce the generation of bubbles and wrinkles, and improve the uniformity and density of the cathode catalyst layer and the anode catalyst layer. In some embodiments, the first flat layer and the second flat layer are made of porous materials. The presence of the porous material further facilitates the discharge of bubbles from the interfacial gaps between the proton exchange membrane and the cathode catalyst layer and the anode catalyst layer during the hot pressing process, increases the interfacial contact area, and further increases the transfer rate of the cathode catalyst layer and the anode catalyst layer. As an example, the porous material includes carbon paper, carbon cloth, high-temperature paper, etc.; in other embodiments, the first flat layer and the second flat layer can also be made of other materials, such as thin steel plates, etc.

[0046] In some embodiments, the area of ​​the first and second tiled layers is greater than or equal to the area of ​​the proton exchange membrane, which balances the forces on each point of the cathode catalyst layer and the anode catalyst layer and improves the transfer rate of the catalyst layer.

[0047] In some embodiments, the thickness of the first tiling layer and the second tiling layer is 10 μm to 300 μm.

[0048] S3, removing the first transfer substrate and the second transfer substrate in the product of step S2, pasting carbon paper on both sides, sealing the frame, and obtaining a membrane electrode after stamping.

[0049] Another aspect of the present invention provides a membrane electrode assembly prepared by the above-mentioned preparation method.

[0050] Another aspect of the present invention provides a fuel cell, which comprises the aforementioned membrane electrode assembly.

[0051] The technical features of the present invention are described in detail below through examples and drawings. Unless otherwise specified, the instruments and materials described in the following examples can be obtained from commercial channels.

[0052] Example 1

[0053] This embodiment provides a method for preparing a membrane electrode by one-step two-stage hot pressing transfer, comprising:

[0054] S1, preparing a cathode catalyst layer and an anode catalyst layer.

[0055] A 60% Pt / C cathode catalyst slurry was coated on a glass fiber paper with a thickness of 100 μm (i.e., the first transfer substrate) by a slit coating method to obtain a glass fiber paper coated with a 60% Pt / C cathode catalyst layer; a 20% Pt / C anode catalyst slurry was coated on a glass fiber paper with a thickness of 100 μm (i.e., the second transfer substrate) to obtain a glass fiber paper coated with a 20% Pt / C anode catalyst layer, and the platinum loadings of the anode catalyst layer and the cathode catalyst layer were 0.1 mg Pt / cm 2 and 0.5mgPt / cm 2 .

[0056] S2, sequentially performing the first hot pressing treatment and the second hot pressing treatment

[0057] The first flat layer, the second transfer substrate coated with the anode catalyst layer, the proton exchange membrane (60 μm), the first transfer substrate coated with the cathode catalyst layer, and the second flat layer are stacked and laid on the hot press in sequence, and the hot press transfer parameters are set before transfer. The first hot press treatment stage: temperature 150 ° C, pressure 5 kg / cm 2 , time is 120 seconds; second hot pressing stage: temperature is 150℃, pressure is 30kg / cm 2 , time is 30 seconds, and transfer is performed.

[0058] S3, finally performing membrane electrode forming: removing the first transfer substrate and the second transfer substrate of the product of step S2, pasting carbon paper on both sides, sealing the frame, and obtaining the membrane electrode after stamping.

[0059] Example 2

[0060] Compared with Example 1, the processing temperatures of the first hot pressing treatment and the second hot pressing treatment in Example 2 are different from those in Example 1, and other preparation conditions and parameters are the same as those in Example 1. Specifically, in Example 2, the first hot pressing treatment stage: the temperature is 130°C, the pressure is 5kg / cm 2 , time is 120 seconds; second hot pressing stage: temperature is 130℃, pressure is 30kg / cm 2 , time is 30 seconds.

[0061] Example 3

[0062] Compared with Example 1, the treatment pressure of the second hot pressing treatment in Example 3 is different from that in Example 1, and other preparation conditions and parameters are the same as those in Example 1, including the first hot pressing treatment conditions in Example 3 are also the same as those in Example 1. Specifically, in Example 3, the first hot pressing treatment stage: temperature is 150°C, pressure is 5kg / cm 2 , time is 120 seconds; second hot pressing stage: temperature is 150℃, pressure is 80kg / cm 2 , time is 30 seconds.

[0063] Comparative Example 1

[0064] Compared with Example 1, Comparative Example 1 does not use two-stage hot pressing treatment. The specific hot pressing treatment conditions are: temperature 150°C, pressure 30kg / cm 2 , the time is 150 seconds. Other preparation conditions and parameters are the same as those in Example 1.

[0065] Comparative Example 2

[0066] First, a cathode catalyst layer and an anode catalyst layer were prepared. A 60% Pt / C catalyst slurry was slit coated on carbon paper to obtain a cathode catalyst layer. A 20% Pt / C catalyst slurry was coated on carbon paper to obtain an anode catalyst layer. The platinum loadings of the anode catalyst layer and the cathode catalyst layer were 0.1 mg Pt / cm 2 and 0.5mgPt / cm 2 ; Then the anode catalyst layer and the cathode catalyst layer are respectively attached to the two sides of the proton exchange membrane, and hot pressing and membrane electrode forming are performed to obtain a common GDE membrane electrode.

[0067] Figures 2 to 5 The following are the actual images of the membrane electrode after the transfer process of Examples 1-3 and Comparative Example 1. The results show that the transfer rates of the cathode catalyst layer and the anode catalyst layer are significantly different under the hot pressing treatment conditions of different temperatures and pressures. In Comparative Example 1, a large part of the catalyst layer (the black part in the figure represents the catalyst layer) is not transferred to the proton exchange membrane ( Figure 5 ), and compared with comparative example 1, the transfer rate of the catalyst layer of the membrane electrode prepared in examples 1-3 of the present invention is significantly improved ( Figure 2-Figure 4), especially Example 1, the transfer rate of Example 1 reaches 100%.

[0068] Figure 6 The thickness of the membrane electrode after the transfer process of Examples 1-3 and Comparative Example 1 is shown. Analysis shows that the greater the treatment pressure and the longer the treatment time, the thickness of the cathode catalyst layer and the anode catalyst layer will be lost, resulting in a decrease in the porosity of the catalyst layer, thereby affecting the performance of the membrane electrode. The membrane electrode prepared in Examples 1 and 2 of the present invention has less thickness loss, which is conducive to ensuring the performance of the membrane electrode.

[0069] In addition, the performance of a 2cm*2cm single cell was tested under hydrogen and oxygen conditions to characterize the performance of the membrane electrode samples of Example 1 and Comparative Examples 1-2 in actual fuel cell stacks. The steps for the polarization curve performance test are as follows: (1) Set the test conditions except the back pressure: battery temperature 60°C, anode / cathode flow, etc.; (2) Start loading and activation, while slowly increasing the back pressure to 100kPa; (3) After activation is completed (the voltage fluctuates within ±1mV within 60 minutes), reduce the load of the single cell to 0A (load reduction range 1A); (4) Adjust the anode / cathode flow so that the back pressure is maintained at around 100kPa, in increments of 10mA, for 1 minute, and use a multimeter to measure 0-0.4A (10-100mA / cm 2 ) and record the voltage at the current density. In increments of 50 mA, hold for 1 minute and use a multimeter to measure 0.4-2.0A (100-500mA / cm 2 ) and record the voltage at the current density. In increments of 100 mA, hold for 1 minute and use a multimeter to measure 2.0-12.0A (500-3000mA / cm 2 ) and record the voltage at the current density.

[0070] The results are as follows Figure 7 As shown in the figure, the performance of the samples in Example 1 and Comparative Example 2 in the activation polarization zone is basically the same, but starting from the ohmic polarization zone, the performance of the transferred CCM membrane electrode prepared in Example 1 is higher than that of the traditional GDE membrane electrode, and it is more obvious in the mass transfer polarization zone, 2000mA cm -2 The power densities are 1108 and 1000 mW / cm 2 , the difference between the two reaches 108mW / cm 2 In addition, the peak power of the membrane electrode of Comparative Example 1 after long-term high-voltage treatment is only 586mW / cm 2 , indicating that the membrane electrode prepared by the method of Example 1 of the present invention has better performance.

[0071] In summary, the present invention provides a method for preparing a membrane electrode by one-step two-stage hot pressing transfer. The method of the present invention can improve the transfer rate of the catalyst layer while retaining the initial pore structure of the catalyst layer to the greatest extent, thereby improving the peak power density of the membrane electrode.

[0072] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a membrane electrode by one-step two-stage hot pressing transfer, characterized in that: The following steps are involved: S1, coating a cathode catalyst slurry onto a first transfer substrate to form a cathode catalyst layer, and coating an anode catalyst slurry onto a second transfer substrate to form an anode catalyst layer; S2, stacking and laying the first tiling layer, the second transfer substrate with the anode catalyst layer formed thereon, the proton exchange membrane, the first transfer substrate with the cathode catalyst layer formed thereon, and the second tiling layer on a hot press in sequence, and performing a first hot pressing treatment and a second hot pressing treatment in sequence, wherein the cathode catalyst layer and the anode catalyst layer are arranged close to the proton exchange membrane; The processing pressure of the first hot pressing treatment is less than the processing pressure of the second hot pressing treatment, and the processing time of the first hot pressing treatment is greater than or equal to the processing time of the second hot pressing treatment.

2. The method for preparing a membrane electrode by one-step two-stage hot pressing transfer as claimed in claim 1, characterized in that: The pressure of the first hot pressing treatment is 1 kg / cm 2 -10kg / cm 2 , the temperature is 120℃-170℃, and the processing time is 60 seconds-300 seconds.

3. The method for preparing a membrane electrode by one-step two-stage hot pressing transfer according to claim 1, characterized in that: The pressure of the second hot pressing treatment is 10 kg / cm 2 -80kg / cm 2 , the temperature is 120℃-170℃, and the processing time is 10 seconds-60 seconds.

4. The method for preparing a membrane electrode by one-step two-stage hot pressing transfer as claimed in claim 1, characterized in that: The first flat layer and the second flat layer include: any one of carbon paper, carbon cloth, high temperature paper or thin steel plate.

5. The method for preparing a membrane electrode by one-step two-stage hot pressing transfer as claimed in claim 1, characterized in that: The areas of the first tiling layer and the second tiling layer are greater than or equal to the area of ​​the proton exchange membrane.

6. The method for preparing a membrane electrode by one-step two-stage hot pressing transfer as claimed in claim 1, characterized in that: The thickness of the first tiling layer and the second tiling layer is 10 μm to 300 μm.

7. The method for preparing a membrane electrode by one-step two-stage hot pressing transfer according to claim 1, characterized in that: The thickness of the proton exchange membrane is 40 μm to 160 μm.

8. The method for preparing a membrane electrode by one-step two-stage hot pressing transfer as claimed in claim 1, characterized in that: In step S1, the cathode catalyst slurry and the anode catalyst slurry are coated on the first transfer substrate and the second transfer substrate respectively by slit coating.

9. The method for preparing a membrane electrode by one-step two-stage hot pressing transfer as claimed in claim 1, characterized in that: Also includes: S3, removing the first transfer substrate and the second transfer substrate in the product of step S2, pasting carbon paper on both sides, sealing the frame, and obtaining a membrane electrode after stamping.

10. A membrane electrode assembly, characterized in that: The membrane electrode is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method and device for fuel cell membrane electrodes

    CN110265671A

  • Preparation of integrated membrane electrode capable of reducing interface impedance

    CN114597460A

  • Membrane electrode assembly and preparation method and application thereof

    CN116190732A

  • Membrane electrode preparation method

    CN117976921A

  • Method of manufacturing membrane electrode structure

    JP2011154969A

Cited By

  • Fuel cell membrane electrode based on cathode catalyst layer prepressing treatment and preparation method thereof

    CN122025669A